A prática assistencial na rede de enfrentamento da violência contra as mulheres em Palmas/TO - Pacheco, Leonora Rezende (2015)
The combating of violence against women must be done by the work that involves the health, legal, police and psychosocial areas in an intersectoral network, because it is a complex and multifactorial phenomenon. The nurse belongs to the health area and the care practice is essential in the confronting of violence.This study aims to: analyze the meanings of violence against women by professionals of Network of Violence Against Women Combat, Understand the operations of the Network of Violence Against Women Combat according to its professionals, analyze the nurse assistance in Network of Violence Against Women Combat by the professionals and nurses from the network. The theoretical categories for data analysis contemplated the concepts of violence against women, the practice of the nurse, the historic route of the nursing work in Brazil and the operationalization of Network of Violence Against Women Combat; passing by authors like: Lenore Walker, Hannah Arendt and Karl Marx. It is a Social Research in Strategic Mode on a qualitative form. The data were collected through semi-structured interview with 21 professionals from 15 institutions that composed the Network of Violence Against Women Combat of Palmas/TO, and by observation of the field. Data analysis was based on thematic content analysis, emerging three thematic categories: "Meanings of violence against women", treating about the meanings, concepts and forms of violence for the participants; "Understanding the Network of Violence Against Women Combat" describing the operation of the network, its barriers and solutions; "The meanings of nurse's practice assistance in the Network of Violence Against Women Combat", participants showed how nurses were performing their practice assistance in the fighting of violence against women. After analyzing the barriers in the functioning of Network of Violence Against Women Combat and the aspects recommended by the literature and public political, a model/flowchart of network operating was proposed in a integrate and cross-sectoral way. The research concluded that for the implementation of networking is necessary to sensitize professionals and nurses about his role in the fighting of violence against women, making them recognize that the network service depends on the co-responsibility, initiative, communication and partnership of each of them. The network consists of institutions, and these by their professionals that should act effectively. Also offered subsidies for nurses practice, as well for other professionals from several sectors, in the establishment of coherent, solving and transforming actions for the prevention, detection and care of women in situations of violence. The training and inclusion of the issue of violence in the formation of professionals are very important. This research contributed to the Network of Violence Against Women Combat of Palmas, in the sensitize of professionals, recognition of partners and communication between them.